2019
DOI: 10.1021/acs.macromol.9b00165
|View full text |Cite
|
Sign up to set email alerts
|

Dopant-Free Hole-Transporting Polymers for Efficient and Stable Perovskite Solar Cells

Abstract: A series of novel polymers (P1–P6) derived from the combination of different units (including thiophene, triarylamine, and spirobifluorene) were successfully synthesized, completely characterized, and used as hole-transporting materials (HTMs) for perovskite solar cells (PSCs). Solar cells with some of these materials as HTMs showed very good performances of almost 13% (12.75% for P4 and 12.38% for P6) even without additives, and devices based on these new HTMs show relatively improved stability against temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 40 publications
(57 reference statements)
1
35
0
1
Order By: Relevance
“…Data in Table confirm this trend since P2 cells have lower R S and higher R SH (nearly one order of magnitude) than the P1 ‐based cells. As observed in earlier reports, a low FF is an indicator of low mobility and conductivity of the material . The intermolecular charge transport is enhanced upon thionation, as demonstrated in Section , thus explaining the increase in the FF of the corresponding DTPP‐based photovoltaic devices.…”
Section: Resultssupporting
confidence: 70%
“…Data in Table confirm this trend since P2 cells have lower R S and higher R SH (nearly one order of magnitude) than the P1 ‐based cells. As observed in earlier reports, a low FF is an indicator of low mobility and conductivity of the material . The intermolecular charge transport is enhanced upon thionation, as demonstrated in Section , thus explaining the increase in the FF of the corresponding DTPP‐based photovoltaic devices.…”
Section: Resultssupporting
confidence: 70%
“…It might be attributed to hydrophilic TEG groups in the alkoxy‐PTEG. However, when considering the high humidity condition and other recent dopant‐free HTMs, the stability data seem very good . The encapsulated alkoxy‐PTEG device was also tested at the same ambient conditions (Figure S15, Supporting Information).…”
Section: Resultsmentioning
confidence: 95%
“…However, the introduction of dopants or additives not only complicates the device preparation process and increases the fabrication costs, but also leads to an enlarged stability problem. For example, it has been reported that the Li‐TFSI dopant and 4‐ tert ‐butylpyrifine (TBP) additive can lead to the formation of high density of pinholes in the spiro‐OMeTAD layer and the redistribution of the Li‐TFSI dopant . In addition, the Li‐TFSI dopant and TBP additive have been reported to accelerate the degradation of PSCs due to their hygroscopic properties …”
Section: Recent Important Progresses On Interfacial Materialsmentioning
confidence: 99%